Diaphragm and preparation method thereof, secondary battery and electric device
By providing the first coating and the second coating in the secondary battery separator, the uneven deposition and SEI thickening problems caused by the metal lithium negative electrode are solved, the circulation and safety performance of the secondary battery are improved, and the lithium element is realized Uniform deposition and mechanical strength increase.
Patent Information
- Application Number
- CN202411513594.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-03
- Estimated Expiration
- 2044-10-28
AI Technical Summary
In secondary batteries, the rough microscopic surface of the metal lithium negative electrode leads to uneven electric field distribution, resulting in uneven deposition and peeling, thickening of SEI, increasing impedance, poor safety performance, and puncture of lithium dendrites into the diaphragm causes safety problems.
The first coating and the second coating are arranged in sequence on one side of the base film of the separator. The first coating increases the mechanical strength. The lithium ion flux at the uniform interface of the second coating is used to utilize the zinc element generated in situ to reduce the uniform electric field of the zinc element. Small lithium deposition overpotential promotes uniform deposition of lithium and reduces the impact of interface rupture caused by volume expansion.
The cycling and safety performance of secondary batteries is improved, and the risk of SEI rupture is reduced by uniform lithium deposition and reducing the battery life, and the mechanical strength of the diaphragm and the uniformity of lithium elements are enhanced.
Smart Images

Figure CN119253200A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the field of secondary batteries, and in particular to a diaphragm and a preparation method thereof, a secondary battery and an electrical device. Background Art
[0002] In secondary batteries, the metal lithium negative electrode has defects and a rough microscopic surface, which causes uneven electric field distribution, resulting in uneven deposition and peeling during the charge and discharge process of the secondary battery, repeated formation of dendrites that pierce the solid electrolyte interface (SEI) to generate new SEI, causing the SEI to continue to thicken, and some lithium dendrites to melt and become inactivated, forming dead lithium accumulation. In addition, the volume expansion and contraction of the metal lithium negative electrode side will also cause the SEI to continue to rupture, resulting in increased impedance, difficulty in secondary electrolyte infiltration, deterioration of cycle performance, and lithium dendrites may pierce the diaphragm, causing safety issues. Summary of the invention
[0003] The present application aims to solve one of the technical problems in the related art at least to some extent.
[0004] On the one hand, the present application proposes a diaphragm, which uses a first coating and a second coating to be sequentially arranged on one side of a base film, and utilizes the first coating to enhance the overall mechanical strength of the diaphragm; the second coating enables the diaphragm to have a uniform lithium ion flux at the interface during application, and at the same time, the in-situ generated zinc element is a lithium-philic material that can uniformly form the electric field at the interface and reduce the overpotential of lithium deposition.
[0005] On the other hand, the present application proposes a method for preparing a diaphragm. The preparation method provided by the present application can realize the preparation of the diaphragm under a simple process.
[0006] On the other hand, the present application proposes a secondary battery, in which a separator with high mechanical strength and capable of promoting uniform deposition of lithium is applied to the secondary battery, thereby obtaining a secondary battery with good cycle performance and safety performance.
[0007] The last aspect of the present application proposes an electrical device, in which a diaphragm with high mechanical strength and the ability to promote uniform lithium deposition is applied to a secondary battery, and the obtained secondary battery is assembled and applied to the electrical device to improve the cycle performance and safety performance of the electrical device.
[0008] According to an embodiment of the first aspect of the present application, a diaphragm is proposed, which includes a base film and a first coating and a second coating arranged in sequence on one side of the base film; the first coating includes an inorganic material and a first binder in a mass ratio of (60-95): (5-40); the second coating includes zinc fluoride, polyacrylic acid, and a second binder in a mass ratio of (40-80): (20-60): (1-5).
[0009] In some embodiments, the thickness of the first coating is L1; 2 μm ≤ L1 ≤ 10 μm;
[0010] and / or, the thickness of the second coating is L2; 1 μm≤L2≤5 μm;
[0011] And / or, the first coating layer and the second coating layer have the same thickness.
[0012] In some embodiments, the particle size of the inorganic material is 200 nm-10 μm;
[0013] And / or, the inorganic material includes at least one of aluminum oxide, silicon dioxide, titanium oxide, zinc oxide, magnesium oxide, hafnium dioxide, tin oxide, zirconium oxide, and a solid electrolyte material;
[0014] The relative molecular weight of the first binder is 400,000-2,000,000;
[0015] And / or, the first binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, copolymer of vinylidene fluoride-trichloroethylene, polyacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, copolymer of acrylonitrile-styrene-butadiene, polyvinyl alcohol, and copolymer of styrene-butadiene.
[0016] In some embodiments, the particle size of the zinc fluoride is 200 nm-10 μm;
[0017] And / or, the relative molecular weight of the polyacrylic acid is 10,000-400,000;
[0018] And / or, the relative molecular weight of the second binder is 400,000-2,000,000;
[0019] And / or, the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and trichloroethylene, a polyacrylate, a polyacrylate salt, a polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, a copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyvinyl alcohol, and a styrene-butadiene copolymer.
[0020] In some embodiments, the base film includes a PP film and / or a PE film;
[0021] And / or, the base film has a thickness of 5-20 μm.
[0022] Among them, the present application sequentially arranges a first coating and a second coating on one side of the base film. The first coating can enhance the mechanical strength of the diaphragm, prevent dendrite growth from piercing the diaphragm, and increase the liquid retention on the lithium negative electrode side to reduce the impact of increased impedance caused by volume expansion; the zinc fluoride in the second coating will in situ generate an intermediate interface layer of LiF and Zn with metallic lithium during the charge and discharge process, and polyacrylic acid and lithium elements will generate highly elastic and highly ion-conductive PAA-li. LiF and PAA-li, an organic-inorganic hybrid fast ion conductor, can not only uniformly distribute lithium ion flux at the interface, but also have good mechanical strength and viscoelasticity to adapt to the volume expansion and contraction of the negative electrode. At the same time, the in-situ generated zinc metal is a lithium-philic metal material, which uniformly distributes the electric field at the interface and reduces the overpotential of lithium element deposition. The two work together to promote uniform deposition of lithium elements and reduce the impact of interface SEI rupture caused by volume expansion.
[0023] According to an embodiment of the second aspect of the present application, a method for preparing a diaphragm is provided, comprising the following steps:
[0024] Dispersing an inorganic material and a first binder in a solvent according to a stoichiometric ratio to obtain a first slurry;
[0025] Dispersing zinc fluoride, polyacrylic acid and a second binder in a solvent according to a stoichiometric ratio to obtain a second slurry;
[0026] Applying the first slurry on the base film and curing it to obtain a first coating; applying the second slurry on the first coating and curing it to obtain a second coating;
[0027] Cut into corresponding sizes to obtain the diaphragm described in any of the above embodiments.
[0028] In some embodiments, the solvent in the first slurry and the second slurry is the same, and both include at least one of N-methylpyrrolidone, formamide, methanol, ethanol, propanol, acetone, dioxane, and tetrahydrofuran;
[0029] And / or, the solid content of the first slurry and the second slurry is the same and is 10%-30%.
[0030] In some embodiments, the curing parameters of the first slurry and the second slurry are: temperature of 80-95° C., time of 4-10 h, and vacuum degree ≤-90 Kpa.
[0031] The preparation method of the present application is to apply the prepared first slurry on the base film and solidify it to form a first coating layer; and then apply the second slurry on the first coating layer and solidify it. The process is simple and can be easily promoted.
[0032] According to an embodiment of the third aspect of the present application, a secondary battery is provided, which includes the separator described in any of the above embodiments.
[0033] In some embodiments, the secondary battery further comprises a positive electrode sheet, a negative electrode sheet and a battery cell; wherein the second coating is in contact with the negative electrode sheet; and the negative electrode sheet is a lithium-copper composite strip.
[0034] In some embodiments, a hot pressing process is used to make the second coating layer fit and contact the negative electrode plate; the hot pressing process parameters are: temperature of 60-100° C., pressure of 600-1200 KG, and holding time of 30-120 s.
[0035] The present invention uses a hot pressing process to bond the second coating to the negative electrode to realize the assembly of the secondary battery, and applies a diaphragm with high mechanical strength and the ability to promote uniform deposition of lithium elements to the secondary battery, thereby obtaining a secondary battery with good cycle performance and safety performance.
[0036] According to an embodiment of the fourth aspect of the present application, an electrical device is provided, which includes the secondary battery described in any of the above embodiments.
[0037] The present application applies a diaphragm with high mechanical strength and the ability to promote uniform deposition of lithium elements to a secondary battery, and assembles the obtained secondary battery into an electrical device to improve the cycle performance and safety performance of the electrical device.
[0038] Additional aspects and advantages of the present application will be given in part in the description below, and in part will become apparent from the description below, or will be learned through the practice of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0039] The above and / or additional aspects and advantages of the present application will become apparent and easily understood from the following description of the embodiments in conjunction with the accompanying drawings, in which:
[0040] Figure 1 It is a schematic diagram of the structure of a diaphragm provided in one embodiment of the present application.
[0041] 1. Base film; 2. First coating; 3. Second coating. DETAILED DESCRIPTION
[0042] Embodiments of the present application are described in detail below, and examples of the embodiments are shown in the accompanying drawings, wherein the same or similar reference numerals throughout represent the same or similar elements or elements with the same or similar functions. The embodiments described below with reference to the accompanying drawings are exemplary and are only used to explain the present application, and cannot be construed as limiting the present application. On the contrary, the present application includes all changes, modifications and equivalents that fall within the spirit and connotation of the appended claims.
[0043] "Scope" disclosed in the present application is limited in the form of lower limit and upper limit, and a given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of a special range. The scope limited in this way can be including end values or not including end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a scope. For example, if the scope of 60-120 and 80-110 is listed for a specific parameter, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range values 1 and 2 are listed, and if the maximum range values 3, 4 and 5 are listed, the following scope can be all expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In the present application, unless otherwise specified, the numerical range "ab" represents the abbreviation of any real number combination between a and b, wherein a and b are real numbers. For example, the numerical range "0-5" means that all real numbers between "0-5" are listed in this document, and "0-5" is just an abbreviation of these numerical combinations. In addition, when a parameter is expressed as an integer ≥ 2, it is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0044] In the description of the embodiments of the present application, the term "and / or" is only a description of the association relationship of the associated objects, indicating that there may be three relationships. For example, A and / or B can represent: A exists alone, A and B exist at the same time, and B exists alone. In addition, the character " / " in this article generally indicates that the associated objects before and after are in an "or" relationship.
[0045] To achieve the above-mentioned purpose, according to an embodiment of the first aspect of the present application, a diaphragm is proposed, which includes a base film and a first coating and a second coating arranged in sequence on one side of the base film; the first coating includes an inorganic material and a first binder in a mass ratio of (60-95): (5-40); the second coating includes zinc fluoride, polyacrylic acid and a second binder in a mass ratio of (40-80): (20-60): (1-5).
[0046] The diaphragm includes a base film 1 and a first coating layer 2 and a second coating layer 3 sequentially arranged on one side of the base film 1. In other words, the base film 1 includes an upper surface at the top and a lower surface at the bottom. The first coating layer 2 and the second coating layer 3 can be sequentially arranged on the upper surface or the lower surface; Figure 1 As shown, the description is given by taking the up and down directions in the figure as an example.
[0047] The base film 1 includes a PP film and / or a PE film, and a first coating layer 2 and a second coating layer 3 are sequentially arranged on the upper surface of the base film 1, wherein in some embodiments the base film thickness is 5-20 μm, and for example, the base film thickness is 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm, 11 μm, 12 μm, 13 μm, 14 μm, 15 μm, 16 μm, 18 μm, 20 μm, etc.
[0048] In some embodiments, the thickness of the first coating is L1; 2μm≤L1≤10μm; for example, the thickness of the first coating is 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. The first coating includes an inorganic material and a first binder in a mass ratio of (60-95): (5-40). The mass ratio of the inorganic material and the first binder in the first coating is (60, 70, 80, 90, 95,): (5, 10, 15, 20, 25, 30, 35, 40). When the proportion of the first binder in the first coating is too high, the porosity of the first coating itself will be reduced, and the liquid retention effect will not be achieved. During the application of the formed diaphragm, when the battery cell is cycled, the volume expansion and contraction on the negative electrode side cannot be supplemented and infiltrated by the electrolyte of the negative electrode side diaphragm, thereby increasing the impedance. Furthermore, the thickness of the first coating is an inert coating. If it is too thick, it will easily increase the internal resistance of the battery cell. When it is 2μm, the mechanical strength of the diaphragm can be greatly improved.
[0049] The inorganic materials include at least one of aluminum oxide, silicon dioxide, titanium oxide, zinc oxide, magnesium oxide, hafnium dioxide, tin oxide, zirconium oxide, and solid electrolyte materials; further, the inorganic material is aluminum oxide, which is an inorganic rigid particle and has mechanical strength in itself. Using aluminum oxide as a coating material is more mature and cheaper; the solid electrolyte materials include lithium titanium phosphate solid electrolyte (LATP), lithium zirconium oxide / lithium lanthanum zirconate (LLZO), lithium lanthanum titanium oxide (LLTO), etc.
[0050] In some embodiments, the particle size of the inorganic material is 200nm-10μm; further, the particle size of the inorganic material is 100nm-1μm, for example, the particle size of the inorganic material is 100nm, 200nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. The particle size of the inorganic material exemplified in this application is not easy to agglomerate and is better processed, and the first coating formed has a higher uniformity. When the particle size of the inorganic material is small, such as less than 200nm, the inorganic material is not conducive to processing and is easy to agglomerate, and the smaller the particle size, the higher the tap density, and the lower the porosity after film formation, which is not conducive to liquid retention; and the smaller the particle size of the inorganic material, the larger the specific surface area, the greater the amount of the first binder used, and at this time, when the first binder content is small, it is easy to lose powder. In addition, when the particle size of the inorganic material is large, such as greater than 10μm, it affects the flatness and uniformity of the first coating.
[0051] In some embodiments, the first binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, copolymer of vinylidene fluoride-trichloroethylene, polyacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl amylopectin, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, amylopectin, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, copolymer of acrylonitrile-styrene-butadiene, polyvinyl alcohol, and copolymer of styrene-butadiene. Further, the first binder is polyvinylidene fluoride.
[0052] In some embodiments, the relative molecular weight of the first binder is 400,000-2 million; further, the relative molecular weight of the first binder is 800,000-1.5 million, for example, the relative molecular weight of the first binder is 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 100, 100, 120, 130, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 2 million, etc. When the molecular weight of the first binder is too large, for example, greater than 2 million, the higher the crystallinity and the stronger the viscosity, which is not conducive to slurry leveling and coating process; when the molecular weight of the first binder is too small, its adhesion decreases, which will cause demolding and powdering. Within the scope of this application, the first binder can have adhesion, low crystallinity (reduced ion transfer impedance), and is conducive to processing.
[0053] In some embodiments, the thickness of the second coating is L2; 1μm≤L2≤5μm; for example, the thickness of the second coating is 1μm, 2μm, 3μm, 4μm, 5μm, etc., wherein the second coating is an in-situ reactive coating, and its excessive thickness has low reaction utilization and increases impedance. Further, the thickness of the first coating and the second coating is the same, which can be 2μm. The second coating includes zinc fluoride, polyacrylic acid, and a second binder in a mass ratio of (40-80): (20-60): (1-5), wherein the mass ratio of zinc fluoride, polyacrylic acid, and the second binder in the second coating is (40, 50, 60, 70, 80): (20, 30, 40, 50, 60, 70, 80): (1, 2, 3, 4, 5).
[0054] In some embodiments, the particle size of zinc fluoride is 200nm-10μm, further, the particle size of zinc fluoride is 100nm-200nm, for example, the particle size of zinc fluoride is 100nm, 200nm, 1μm, 2μm, 3μm, 4μm, 5μm, 6μm, 7μm, 8μm, 9μm, 10μm, etc. The zinc fluoride in the present application has a higher reaction specific surface area with metallic lithium at the exemplified particle size.
[0055] In some embodiments, the relative molecular weight of polyacrylic acid is 10,000-400,000; further, the relative molecular weight of polyacrylic acid is 100,000-300,000, for example, the relative molecular weight of polyacrylic acid is 10,000, 50,000, 100,000, 150,000, 200,000, 300,000, 400,000, etc. The polyacrylic acid in the present application has a lower molecular weight and crystallinity at the exemplary particle size and is more easily lithiated.
[0056] In some embodiments, the second binder includes at least one of polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, copolymer of vinylidene fluoride-trichloroethylene, polyacrylate, polyacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl amylopectin, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, amylopectin, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, copolymer of acrylonitrile-styrene-butadiene, polyvinyl alcohol, and copolymer of styrene-butadiene. Further, the second binder is polyvinylidene fluoride.
[0057] In some embodiments, the relative molecular weight of the second binder is 400,000-2 million, further, the relative molecular weight of the second binder is 800,000-1.5 million, for example, the relative molecular weight of the second binder is 400,000, 500,000, 600,000, 700,000, 800,000, 900,000, 100, 100, 120, 130, 140,000, 150,000, 160,000, 170,000, 180,000, 190,000, 2 million, etc. When the molecular weight of the second binder is too large, for example, greater than 2 million, the higher the crystallinity and the stronger the viscosity, which is not conducive to slurry leveling and coating process; when the molecular weight of the second binder is too small, its adhesion decreases, which will cause demoulding and powdering. Within the scope of this application, the second binder can have adhesion, low crystallinity (reduced ion transfer impedance), and is conducive to processing.
[0058] In the embodiment of the present application, the first coating and the second coating are sequentially arranged on one side of the base film, while ensuring the mechanical strength of the diaphragm, the organic-inorganic interface intermediate layer generated in situ cleverly combines the characteristics of high viscoelasticity and high stability, and has high ion conductivity, accelerates ion transmission, uniform ion flux, reduces the negative impact of volume expansion on the negative electrode side, and promotes uniform deposition of lithium ions; the zinc element replaced in situ grows uniformly on the surface of metallic lithium, uniformizing the electric field strength on the negative electrode side, and zinc and its oxides, as lithium-philic materials, reduce the overpotential of lithium element deposition nucleation, and promote uniform deposition of lithium elements. The above materials and structures of this embodiment work together to optimize the lithium metal deposition interface, promote high-quality deposition, directly improve the cycle performance of the battery cell, and indirectly inhibit the formation of dendrites to improve safety.
[0059] According to an embodiment of the second aspect of the present application, a method for preparing a diaphragm is provided, comprising the following steps:
[0060] S1: dispersing an inorganic material and a first binder in a solvent according to a stoichiometric ratio to obtain a first slurry;
[0061] S2: dispersing zinc fluoride, polyacrylic acid and a second binder in a solvent according to a stoichiometric ratio to obtain a second slurry;
[0062] S3: applying the first slurry on the base film and curing it to obtain a first coating; applying the second slurry on the first coating and curing it to obtain a second coating;
[0063] S4: Cutting into corresponding sizes to obtain the diaphragm in any of the above embodiments.
[0064] Among them, in S1, the inorganic material and the first binder are dispersed in the solvent according to the stoichiometric ratio to form a first slurry, and the solid content of the first slurry is 10%-30%, wherein the solid content is the mass percentage of the remaining part of the first slurry after drying under specified conditions; further, the solid content of the first slurry is 20%. When the solid content in the first slurry is too low, such as less than 10%, the content of the inorganic material is too low, and the increase in the overall mechanical strength of the diaphragm is limited; when the solid content in the first slurry is too high, such as higher than 30%, it is not conducive to thin coating. In this embodiment, the solvent includes at least one of N-methylpyrrolidone, formamide, methanol, ethanol, propanol, acetone, dioxane, and tetrahydrofuran.
[0065] In S2, zinc fluoride, polyacrylic acid and a second binder are dispersed in a solvent according to a stoichiometric ratio to form a second slurry, and the solid content of the second slurry is 10%-30%. Further, the solid content of the second slurry is 20%. When the solid content in the second slurry is too low, such as less than 10%, the content of zinc fluoride and polyacrylic acid is too low, which is not conducive to the deposition of lithium elements. When the solid content in the second slurry is too high, such as higher than 30%, it is not conducive to thin coating. In this embodiment, the solvent is the same as the solvent for preparing the first slurry, including at least one of N-methylpyrrolidone, formamide, methanol, ethanol, propanol, acetone, dioxane, and tetrahydrofuran.
[0066] Among them, in S3, the first slurry is coated on the base film with a 5μm scraper height, and then placed in a vacuum oven at 80-95℃ for 4-10h, and the vacuum degree is ≤-90Kpa to obtain the first coating. Further, the curing parameters of the first slurry are 90℃ baking for 8h, and the vacuum degree is -90Kpa. Then the second slurry is coated on the first coating with a 5μm scraper height, and then placed in a vacuum oven at 80-95℃ for 4-10h, and the vacuum degree is ≤-90Kpa to obtain the second coating. Further, the curing parameters of the second slurry are 90℃ baking for 8h, and the vacuum degree is -90Kpa.
[0067] The preparation method in this application is to apply the prepared first slurry on the base film and solidify it to form a first coating; then apply the second slurry on the first coating and solidify it. The process is simple and can be promoted. Therefore, the convenience and quantitative controllability of the diaphragm coating are cleverly utilized to introduce zinc fluoride, polyacrylic acid, and inorganic materials into the metal lithium interface to generate a multifunctional intermediate layer with high uniformity and high stability in situ. Compared with direct non-in-situ treatment on the lithium metal surface, this method is more efficient and convenient, with high feasibility of process scale-up and adjustable degree of treatment.
[0068] According to an embodiment of the third aspect of the present application, a secondary battery is provided, which includes the separator in any one of the above embodiments.
[0069] In some embodiments, the secondary battery further includes a positive electrode plate, a negative electrode plate, and an electrode core; wherein the second coating is attached to and in contact with the negative electrode plate; the negative electrode plate is a lithium-copper composite tape.
[0070] The secondary battery further includes the separator provided in the above embodiments of the present application.
[0071] [Positive electrode plate]
[0072] The positive electrode plate includes a positive current collector and a positive electrode film layer provided on at least one surface of the positive current collector. The positive electrode film layer includes a positive active material, and the proportion of the positive active material is more than 95%. As an example, the positive current collector has two surfaces opposite to each other in its own thickness direction, and the positive electrode film layer is provided on either one or both of the two opposite surfaces of the positive current collector with a double-sided coating surface density of 380 g / m 2 .
[0073] The positive current collector can be a metal foil or a composite current collector. For example, as the metal foil, aluminum foil can be used. The composite current collector can include a polymer material base layer and a metal layer formed on at least one surface of the polymer material base layer. The composite current collector can be formed by forming a metal material (such as aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0074] In some embodiments, the positive active material in the positive electrode plate of the present application can be a positive active material for batteries well-known in the art. As an example, the positive active material can include at least one of the following materials: As an example, the positive active material can include, but is not limited to, lithium iron phosphate (LiFePO4), lithium manganese phosphate (LiMnPO4), lithium cobalt phosphate (LiCoPO4), lithium iron pyrophosphate (Li2FeP2O7), lithium cobalt oxide (LiCoO2), spinel-type lithium manganese oxide (LiMn2O4), spinel-type lithium nickel manganese oxide (LiNi 0.5 Mn 1.5 O4), layered lithium manganese oxide (LiMnO2), lithium nickel oxide (LiNiO2), lithium niobate (LiNbO2), lithium ferrite (LiFeO2), lithium manganate (LiMgO2), lithium calcium oxide (LiCaO2), lithium copper oxide (LiCuO2), lithium zinc oxide (LiZnO2), lithium molybdate (LiMoO2), lithium tantalate (LiTaO2), lithium tungstate (LiWO2), lithium nickel cobalt aluminum oxide (LiNi x Co y Al 1-x-y O2, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, for example LiNi 0.8Co 0.15 Al 0.05 (O2), lithium nickel cobalt manganese oxide (LiNi x Co y Mn 1-x-y O2, 0 < x < 1, 0 < y < 1, 0 < x + y < 1, for example LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, LiNi 0.5 Co 0.2 Mn 0.3 O2, LiNi 0.6 Co 0.2 Mn 0.2 O2, LiNi 0.8 Co 0.1 Mn 0.1 O2, etc.), lithium-rich materials (such as lithium-rich nickel cobalt manganese oxide), manganese oxide (MnO2), vanadium oxide, sulfur oxide, silicate oxide, and at least one of their respective modified compounds. These materials can be used alone or in combination of two or more.
[0075] The modified compounds of the above positive electrode active materials can be doping modification, surface coating modification, or simultaneous doping and coating modification of the positive electrode active materials, etc.
[0076] In some embodiments, the positive electrode film layer may optionally further include a binder. As an example, the binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorinated acrylate resin.
[0077] In some embodiments, the positive electrode film layer may optionally further include a conductive agent. As an example, the conductive agent may include at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers.
[0078] In some embodiments, the positive electrode plate can be prepared by the following method: dispersing the components for preparing the positive electrode plate, such as the positive electrode active material, conductive agent, binder, and any other components in the first aspect of the present application, in a solvent (such as N-methylpyrrolidone) to form a positive electrode slurry; coating the positive electrode slurry on the positive electrode current collector, and after processes such as drying and cold pressing, the positive electrode plate can be obtained.
[0079] [Negative electrode plate]
[0080] The negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector, wherein the negative electrode film layer includes a negative electrode active material. As an example, the negative electrode current collector has two surfaces opposite to each other in its own thickness direction, and the negative electrode film layer is disposed on any one or both of the two opposite surfaces of the negative electrode current collector.
[0081] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. For example, as the metal foil, a copper foil may be used. The composite current collector may include a polymer material base layer and a metal layer formed on at least one surface of the polymer material substrate. The composite current collector may be formed by forming a metal material (copper, copper alloy, nickel, nickel alloy, titanium, titanium alloy, silver and silver alloy, etc.) on a polymer material substrate (such as a substrate of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), polyethylene (PE), etc.).
[0082] In some embodiments, the negative electrode active material may adopt the negative electrode active material for the battery known in the art. As an example, the negative electrode active material may include at least one of the following materials: metallic lithium, artificial graphite, natural graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, lithium titanate, etc. The silicon-based material may be selected from at least one of elemental silicon, silicon oxide compounds, silicon-carbon composites, silicon-nitrogen composites, and silicon alloys. The tin-based material may be selected from at least one of elemental tin, tin oxide compounds, and tin alloys. However, the present application is not limited to these materials, and other traditional materials that can be used as negative electrode active materials for batteries may also be used. These negative electrode active materials may be used alone or in combination of two or more.
[0083] In some embodiments, the negative electrode film layer may further include a binder. The binder may be selected from at least one of styrene-butadiene rubber (SBR), polyacrylic acid (PAA), sodium polyacrylate (PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), polymethacrylic acid (PMAA) and carboxymethyl chitosan (CMCS).
[0084] In some embodiments, the negative electrode film layer may further include a conductive agent, which may be selected from at least one of superconducting carbon, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene and carbon nanofibers.
[0085] In some embodiments, the negative electrode film layer may optionally include other additives, such as a thickener (eg, sodium carboxymethyl cellulose (CMC-Na)).
[0086] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as deionized water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, cold pressing and other processes, the negative electrode sheet can be obtained.
[0087] [Electrolytes]
[0088] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present application has no specific restrictions on the type of electrolyte, which can be selected according to needs. For example, the electrolyte can be liquid, gel or all-solid.
[0089] In some embodiments, the electrolyte is an electrolyte solution, which includes an electrolyte salt and a solvent.
[0090] In some embodiments, the electrolyte salt can be selected from at least one of lithium hexafluorophosphate, lithium tetrafluoroborate, lithium perchlorate, lithium hexafluoroarsenate, lithium bis(fluorosulfonyl)imide, lithium bis(trifluoromethanesulfonyl)imide, lithium trifluoromethanesulfonate, lithium difluorophosphate, lithium difluorooxalatoborate, lithium dioxalatoborate, lithium difluorodioxalatophosphate, and lithium tetrafluorooxalatophosphate.
[0091] In some embodiments, the solvent can be selected from at least one of ethylene carbonate, propylene carbonate, ethyl methyl carbonate, diethyl carbonate, dimethyl carbonate, dipropyl carbonate, methyl propyl carbonate, ethyl propyl carbonate, butylene carbonate, fluoroethylene carbonate, methyl formate, methyl acetate, ethyl acetate, propyl acetate, methyl propionate, ethyl propionate, propyl propionate, methyl butyrate, ethyl butyrate, 1,4-butyrolactone, cyclopentane sulfone, dimethyl sulfone, methyl ethyl sulfone and diethyl sulfone.
[0092] In some embodiments, the electrolyte may further include additives, such as negative electrode film-forming additives, positive electrode film-forming additives, and additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high or low temperature performance, etc.
[0093] In some embodiments, the positive electrode sheet, the negative electrode sheet and the separator can be made into an electrode assembly by a winding process or a lamination process. For example, the positive electrode sheet, the negative electrode sheet and the separator are cut into corresponding sizes, and the 5Ah bare battery cell is subsequently hot pressed, packaged, injected, formed, and divided. The hot pressing process parameters are a temperature of 60-100°C, a pressure of 600-1200KG, and a holding time of 30-120s; further, the hot pressing process parameters are a temperature of 80°C, a pressure of 1000KG, and a holding time of 60s; wherein the injection coefficient is 1.8gAh. This embodiment uses a hot pressing process to fit the second coating to the contacting negative electrode sheet to realize the assembly of the secondary battery, and applies a separator with high mechanical strength and capable of promoting uniform deposition of lithium to the secondary battery, so as to obtain a secondary battery with good cycle performance and safety performance.
[0094] In some embodiments, the secondary battery may include an outer package, which may be used to encapsulate the electrode assembly and the electrolyte.
[0095] In some embodiments, the outer packaging of the secondary battery may be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery may also be a soft package, such as a bag-type soft package. The material of the soft package may be plastic, and examples of the plastic include polypropylene, polybutylene terephthalate, and polybutylene succinate.
[0096] The present application has no particular limitation on the shape of the secondary battery, which may be cylindrical, square, or any other shape.
[0097] According to an embodiment of the fourth aspect of the present application, an electrical device is provided, which includes the secondary battery in any of the above embodiments.
[0098] The present application applies a diaphragm with high mechanical strength and the ability to promote uniform deposition of lithium elements to a secondary battery, and assembles the obtained secondary battery into an electrical device to improve the cycle performance and safety performance of the electrical device.
[0099] To facilitate further understanding of the present application, the scheme of the present application is further described below in conjunction with the embodiments. Those skilled in the art will understand that the description in the present application is only part of the examples, and any other suitable specific examples are within the scope of the present application.
[0100] Example 1
[0101] This embodiment provides a diaphragm, and its preparation method and specific operating parameters are as follows:
[0102] Preparation of the first slurry: Alumina with a particle size of 1 μm and PVDF with a relative molecular weight of 400,000 are dispersed in N-methylpyrrolidone at a mass ratio of 90:10 to obtain a first slurry, wherein the solid content of the first material is 20%.
[0103] Preparation of the second slurry: zinc fluoride with a particle size of 50 nm, polyacrylic acid with a relative molecular weight of 10,000, and PVDF with a relative molecular weight of 400,000 are dispersed in N-methylpyrrolidone in a mass ratio of 50:45:5 to obtain a second slurry, and the solid content of the second slurry is controlled to be 20%.
[0104] Take a conventional 7μm PE base film, apply the first slurry with a 5μm scraper height, and then place it in a vacuum oven for baking at 90℃ for 8h, and the vacuum degree is -90Kpa to obtain a first coating thickness of 2μm; apply the second slurry on the first coating with a 5μm scraper height, and then place it in a vacuum oven for baking at 90℃ for 8h, and the vacuum degree is -90Kpa to obtain a second coating thickness of 2μm, and then cut it into corresponding sizes to obtain a diaphragm.
[0105] Example 2
[0106] This embodiment provides a diaphragm, which is different from Embodiment 1 in the following aspects: when preparing the second slurry, the mass ratio of zinc fluoride, polyacrylic acid and PVDF is 40:55:5.
[0107] Example 3
[0108] This embodiment provides a diaphragm, which has the following differences compared with the embodiment 1: the thickness of the first coating layer is 4 μm.
[0109] Example 4
[0110] This embodiment provides a diaphragm, which has the following differences compared with the embodiment 1: the thickness of the second coating layer is 4 μm.
[0111] Example 5
[0112] This embodiment provides a diaphragm, which is different from the embodiment 1 in the following aspects: the thickness of the first coating layer is 4 μm; the thickness of the second coating layer is 4 μm.
[0113] Example 6
[0114] This embodiment provides a diaphragm, which is different from Embodiment 1 in the following aspects: when preparing the first slurry, the mass ratio of alumina to PVDF is 80:20.
[0115] Example 7
[0116] This embodiment provides a diaphragm, which is different from Embodiment 1 in the following aspects: when preparing the second slurry, the mass ratio of zinc fluoride, polyacrylic acid and PVDF is 60:35:5.
[0117] Comparative Example 1
[0118] This embodiment provides a diaphragm, which is different from Embodiment 1 in the following aspects: a conventional 7 μm PE base film is taken, and the second slurry is coated with a 5 μm scraper height, and then placed in a vacuum oven and baked at 90 degrees for 8 hours, with a vacuum degree of -90 Kpa and a thickness of 2 μm, and then cut into corresponding sizes to obtain a diaphragm.
[0119] Comparative Example 2
[0120] This embodiment provides a diaphragm, which is different from Embodiment 1 in the following aspects: a conventional 7 μm PE base film is taken, and the first slurry is coated with a 5 μm scraper height, and then placed in a vacuum oven and baked at 90 degrees for 8 hours. The vacuum degree is -90 Kpa, and the first coating thickness is 2 μm, which is then cut into corresponding sizes to obtain a diaphragm.
[0121] Comparative Example 3
[0122] This embodiment provides a diaphragm, which is different from the embodiment 1 in the following aspects: a conventional 7 μm PE-based film is cut into corresponding sizes as a diaphragm.
[0123] Comparative Example 4
[0124] This embodiment provides a diaphragm, which has the following differences compared with the embodiment 1: the thickness of the first coating layer is 1 μm; the thickness of the second coating layer is 1 μm.
[0125] Test Case
[0126] The diaphragms prepared in the above-mentioned embodiments and comparative examples were assembled into 5AH laminated batteries for cycle performance testing. The 5AH laminated battery was dispersed in N-methylpyrrolidone (NMP) according to the mass ratio of 95:2:3 of positive electrode active material, conductive agent Super P (manufacturer: Yiruishi) and binder PVDF (manufacturer: Solvay, model: 5130), with a solid content of 70%, and ball milled to form a uniform positive electrode slurry; the positive electrode slurry was coated on the rough surface of a clean aluminum foil with a coater, and the coating surface density was 380g / ㎡, and then placed in a vacuum oven at 120°C for 12 hours to obtain a pole piece with a compaction density of 3.45g / cm 3; Cut into 60mm*110mm pole pieces, and leave corresponding pole ears; the negative electrode adopts lithium copper composite tape, cut into 62mm*112mm, and the diaphragm adopts the diaphragm obtained in the above embodiments and comparative examples, cut into 63mm*113mm; stack 13 layers of positive electrode, 14 layers of negative electrode, and the coating side of the diaphragm are all facing the negative electrode; the obtained bare battery cell is hot pressed, and the hot pressing process parameters are: temperature of 80°C, pressure of 1000KG and holding time of 60s; finally, the hot-pressed battery cell aluminum-plastic film is assembled and packaged to obtain a 5AH soft-pack battery; the electrolyte used is a solution of LiPF6 with a concentration of 1 mol / L obtained by dissolving LiPF6 in a mixed solvent of ethyl carbonate (EC) and diethyl carbonate (DMC) (volume ratio EC:DMC=1:1).
[0127] The cycle test was carried out under a constant pressure of 100KG, a charge and discharge rate of 1C, a voltage of 2.8V-4.3V, a charging method of constant current and constant voltage, a cut-off current of 0.05C, and the cycle was carried out until it decayed to 80% of the initial capacity.
[0128] The DCR of the battery cell at 50% SOC in the first cycle is recorded as R1; the DCR of the battery cell at 50% SOC after 30 cycles is recorded as R2; the test method is: adjust the battery cell to 50% SOC at a rate of 0.33C, let it stand for 30 minutes, record the voltage as V1, then charge it at a rate of 2C for 10 seconds, record the voltage as V2, and the interval between sampling points is 1 second. R = (V2-V1) / 10Ah. The internal resistance growth rate is recorded as K, K = (R2-R1) / R1; K indirectly reflects the degree of system deterioration (volume expansion leading to SEI rupture and regeneration, insufficient electrolyte on the negative electrode side, excessive consumption of electrolyte, etc.).
[0129] The initial thickness of the battery cell is recorded as W, the first cycle full charge thickness is recorded as W1, the 30th cycle full charge thickness is recorded as W2, and the thickness growth rate is recorded as Q, Q = (W2-W1) / W1, Q indirectly reflects the degree of deterioration of the negative electrode interface (lithium dendrites continue to grow, resulting in SEI thickening, dead lithium accumulation, relative density of lithium deposition, etc.). All tests were carried out at room temperature, and the results are shown in Table 1.
[0130] Table 1 Test results of secondary batteries made of diaphragms in various embodiments and comparative examples
[0131]
[0132]
[0133] Compared with Example 1, the K value and Q value of Example 2 increased, and the cycle life was shortened, indicating that the performance began to deteriorate after the PAA content exceeded 45%. It was preliminarily speculated that there were too many organic components in the interface layer generated by the second coating, the mechanical strength decreased, and the stability at the interface was poor.
[0134] Compared with Example 1 and Comparative Example 3, Example K and R are relatively small, and the cycle life is greatly improved, indicating that this double-layer structure achieves the expected effect
[0135] Comparison of Example 1 with Example 2 shows that the effect of Example 1 is better, indicating that the second coating has achieved the in-situ interface effect, which is better than the single first coating.
[0136] Comparison between Example 1 and Example 3, and between Example 2 and Example 3, shows that the cycle life of the examples is improved, and K and Q are reduced, indicating that the mechanical strength and liquid retention effect of the first coating and the in-situ interface of the second coating are beneficial to the battery cycle, which once again proves that the second coating has a more significant effect on the uniform deposition of lithium.
[0137] Comparison between Example 1 and Comparative Example 1 shows that the mechanical strength and liquid retention capacity of the first coating layer further improve the high-quality lithium deposition and cycle performance.
[0138] Comparison between Example 3 and Example 1 shows that when the first coating is thickened to 4 μm, K and initial internal resistance will increase, but Q will not be improved, which will further reduce the cycle life. This proves that the first coating thickness should not be too thick.
[0139] Compared with Example 1, Example 4 has a slightly reduced Q, but a significantly increased K, indicating that the thickening of the second coating will lead to a low lithiation utilization rate, but increase the impedance and reduce the cycle life.
[0140] Compared with Example 1, Example 5 shows that K increases significantly, Q does not increase, and the cycle life decreases. This indicates that thick coatings deteriorate the system to a greater extent.
[0141] Compared with Example 1, K of Comparative Example 4 increases significantly, indicating that the thin coating leads to low quality of lithium element deposition, which will cause SEI to continuously generate and consume electrolyte, and the liquid retention performance is poor; Q also doubles, indicating that the lithium deposition is not dense, and the active lithium is continuously consumed to form dead lithium; at the same time, the cycle life is also shortened. The above shows that the thin coating does not achieve the material structure effect.
[0142] Compared with Example 1, Example 6 has significantly increased K and Q, and a significantly reduced cycle life. It is speculated that the high content of glue in the first coating causes pore blockage in the coating, increases diffusion transmission impedance, and thus deteriorates electrical performance.
[0143] Comparison of Example 7 with Example 1 and Example 2 shows that when the zinc fluoride content is greater than 50%, there is no obvious benefit and the cycle life is slightly lower than that of Example 1. It is speculated that this is caused by excessive zinc fluoride and a high proportion of unreacted conversion.
[0144] Among them, the effect advantage of the second coating is more direct, and it complements the first coating, greatly improving the cycle performance of the electrical device and the quality of lithium element deposition.
[0145] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present application. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0146] Although the embodiments of the present application have been shown and described above, it can be understood that the above embodiments are exemplary and cannot be understood as limitations on the present application. Ordinary technicians in this field can change, modify, replace and modify the above embodiments within the scope of the present application.
Claims
1. A diaphragm, characterized in that: It includes a base film and a first coating layer and a second coating layer sequentially arranged on one side of the base film; the first coating layer includes an inorganic material and a first binder in a mass ratio of (60-95):(5-40); the second coating layer includes zinc fluoride, polyacrylic acid and a second binder in a mass ratio of (40-80):(20-60):(1-5).
2. The diaphragm according to claim 1, characterized in that The thickness of the first coating is L1; 2μm≤L1≤10μm; and / or, the thickness of the second coating is L2; 1 μm≤L2≤5 μm; And / or, the first coating layer and the second coating layer have the same thickness.
3. The diaphragm according to claim 1 or 2, characterized in that: The particle size of the inorganic material is 200nm-10μm; And / or, the inorganic material includes at least one of aluminum oxide, silicon dioxide, titanium oxide, zinc oxide, magnesium oxide, hafnium dioxide, tin oxide, zirconium oxide, and a solid electrolyte material; The relative molecular weight of the first binder is 400,000-2,000,000; And / or, the first binder includes at least one of polyacrylic acid, polyacrylate, polyvinylidene fluoride, copolymer of vinylidene fluoride-hexafluoropropylene, copolymer of vinylidene fluoride-trichloroethylene, polyacrylate, polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, copolymer of acrylonitrile-styrene-butadiene, polyvinyl alcohol, and copolymer of styrene-butadiene.
4. The diaphragm according to claim 1 or 2, characterized in that: The particle size of the zinc fluoride is 200nm-10μm; And / or, the relative molecular weight of the polyacrylic acid is 10,000-400,000; And / or, the relative molecular weight of the second binder is 400,000-2,000,000; And / or, the second binder includes at least one of polyvinylidene fluoride, a copolymer of vinylidene fluoride and hexafluoropropylene, a copolymer of vinylidene fluoride and trichloroethylene, a polyacrylate, a polyacrylate salt, a polyacrylonitrile, polyvinyl pyrrolidone, polyvinyl acetate, a copolymer of ethylene-vinyl acetate, polyimide, polyethylene oxide, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, cyanoethyl sucrose, pullulan, carboxymethyl cellulose, sodium carboxymethyl cellulose, lithium carboxymethyl cellulose, acrylonitrile-styrene-butadiene copolymer, polyvinyl alcohol, and a styrene-butadiene copolymer.
5. The diaphragm according to claim 1 or 2, characterized in that: The base film comprises a PP film and / or a PE film; And / or, the base film has a thickness of 5-20 μm.
6. A method for preparing a diaphragm, characterized in that: The following steps are involved: Dispersing an inorganic material and a first binder in a solvent according to a stoichiometric ratio to obtain a first slurry; Dispersing zinc fluoride, polyacrylic acid and a second binder in a solvent according to a stoichiometric ratio to obtain a second slurry; Applying the first slurry on the base film and curing it to obtain a first coating; applying the second slurry on the first coating and curing it to obtain a second coating; The diaphragm according to any one of claims 1 to 5 is obtained by cutting into corresponding sizes.
7. The preparation method according to claim 6, characterized in that: The solvent in the first slurry and the second slurry is the same, and both include at least one of N-methylpyrrolidone, formamide, methanol, ethanol, propanol, acetone, dioxane, and tetrahydrofuran; And / or, the solid content of the first slurry and the second slurry is the same and is 10%-30%.
8. The preparation method according to claim 6, characterized in that: The curing parameters of the first slurry and the second slurry are: temperature of 80-95° C., time of 4-10 h, and vacuum degree ≤-90 Kpa.
9. A secondary battery, characterized in that: The secondary battery comprises the separator according to any one of claims 1 to 7.
10. The secondary battery according to claim 9, characterized in that: The secondary battery also includes a positive electrode sheet, a negative electrode sheet and a battery cell; wherein the second coating is in contact with the negative electrode sheet; and the negative electrode sheet is a lithium-copper composite strip.
11. The secondary battery according to claim 10, characterized in that: A hot pressing process is used to make the second coating layer fit and contact the negative electrode plate; the hot pressing process parameters are: temperature of 60-100° C., pressure of 600-1200 KG, and holding time of 30-120 s.
12. An electrical device, characterized in that: A secondary battery comprising any one of claims 9 to 11.
Citation Information
Patent Citations
Silicon monoxide / polyacrylic acid modified high-safety battery diaphragm as well as preparation method and application thereof
CN112909433A
Slow-release alkali metal secondary battery diaphragm and preparation method thereof
CN117525748A
Lithium ion battery composite diaphragm and preparation method thereof
CN117613513A
Separator film for secondary battery and method for manufacturing the same
KR1020130007740A
Mask recognition system using facial recognition
KR1020210155877A
